Obstacles to Entrepreneurship in Albania, Georgia, Morocco, Nigeria, and Pakistan - El Alaoui, Aicha; Shopovski, Jovan; Kvirkvaia, Murtaz; Alam, Noor; Ofili, Onyeka Uche (European Scientific Journal, ESJ, 2016)
Entrepreneurship reinforces the economic growth of a country. Therefore, most countries, especially developing ones, are striving to create new policies and implement actions in order to support entrepreneurial processes through the establishment of a business-friendly environment. However, there are still many obstacles facing entrepreneurs in these countries. The aim of this paper is to locate the most common barriers to entrepreneurial processes in Albania, Georgia, Morocco, Nigeria, and Pakistan. Data from officials in 149 companies were collected through questionnaire dissemination from October to December 2015. The company officials have been asked several questions, among which, to rate the obstacles listed, starting from the ones they perceive to be most restrictive for their businesses. Most of the companies examined were small and medium size companies, SMEs. Both a descriptive analysis and a comparative analysis of the data were applied, in order to check the accuracy of the hypothesis established. It was found that state policy towards SMEs and political instability/corruption are the most common obstacles to entrepreneurship in these developing countries. Also, tax policy was also considered as an obstacle to entrepreneurship.